Studi Sistem Pembangkit Listrik Tenaga Surya Off Grid Skala Rumah Tangga pada Daerah Bagan Deli Menggunakan Pvsyst - Ahmad Dani; Dino Erivianto (Jurnal Indonesia Sosial Teknologi, 2022)
Solar energy is a source of energy that will never run out and has almost no negative effects on the environment. In this study using Pvsyst software with Stand Alone/Off Grid PV System conditions. Bagan Deli is one of the kelurahan in Medan Belawan sub-district which is located in a coastal area to analyze the potential for solar energy which is located at latitude 3.7756° north longitude, longitude 98.7033° east longitude. The optimal tilt angle according to the latitude is 10° (Tilt Angle) and the Azimuth angle of 180° (Azimuth Angle) facing south. The PV module used in the simulation is a solar cell module selected from the PVsyst database, namely Si-mono TDB 156X 156-36P 150W. The electricity load per day is 2,625 kWh/day, the need for electricity supply in one year is 958.1 kWh. Through the PVsyst software simulation, the Stand-Alone Solar Panel System uses 4 solar panels with a power of 150Wp, an area of ​​4 m2 and 2 batteries with a capacity of 200 Ah which are installed in series. The results of the performance of the Stand-Alone Solar Panel System obtained unused Energy of 0.2 kWh/kWp/day, Loss on PV Array of 1.12 kWh/kWp/day, Loss on PLTS System of 0.28 kWh/kWp/day, Energy that supplied to the user at 3.05 kWh/kWp/day.